(untitled) ("Temas Sociais" Journal, 2024)
On the centenary of the death of Father António d’Oliveira (1867-1923), we analyze his work and actions in favour of the protection and re-education of juvenile delinquents, especially those interned at the Lisbon House of Correction. He drafted an innovative intervention regulation in this establishment (1901) and was the mentor of the Child Protection Law (1911), which projected the country into the wake of nations concerned with childhood. It is a historical-documentary study using hermeneutic analysis of sources (primary, secondary) and legislation, with the following objectives: analyze his work in the area of ​​child protection; interpret the Child Protection Law in light of the time; understand the re-educational intervention (God, Country, Work) with hospitalized minors. We intend to remember historiographically that this figure is dedicated to the problem of childhood and juvenile delinquency and to raising public awareness of serious social issues, which contributed to the History of (Social) Education.